Analisis Komparatif Puisi Karawang-Bekasi Karya Chairil Anwar Dan Little Gidding V Karya T.S. Eliot - Nita Yuliana; Husnun Hanifah; Roudhatul Janah; Faqih Singgih Partika; Bachtiar Nugroho (PT. Padang Tekno Corp, 2025)
This study aims to analyze and compare two modernist poems from different cultural backgrounds: Karawang-Bekasi by Chairil Anwar and Little Gidding V by T. S. Eliot. The research employs a qualitative-descriptive method using a comparative literature approach. The analysis focuses on thematic structure, imagery, linguistic style, and the social-spiritual functions of the poems. The findings reveal that Karawang-Bekasi emphasizes patriotism, sacrifice, and national spirit through spatial deixis and war imagery, while Little Gidding V presents a spiritual reflection on time, history, and reconciliation through metaphysical symbolism such as fire and the rose. Although both poems explore the themes of death and humanity, their orientations differ: Chairil Anwar constructs a collective national memory, whereas T. S. Eliot emphasizes human transcendence and redemption. This comparative study highlights that cross-cultural literary works can serve as a medium for reflecting universal human values.